Trump Administration Begins to Recognize the Loss of Scientific Integrity: Refuting a Political Hitjob - Herndon, J. Marvin (Advances in Social Sciences Research Journal, 2020)
A recent PLOSONE article utilized tabulations of opinions obtained from federal scientists to assert “perceived losses of scientific integrity under the Trump Administration.” The article presupposes the wide-spread existence of scientific integrity among federal scientists, which I refute based upon documented 40+ years’ experience making fundamental scientific discoveries which the scientific establishment systematically ignores and in instances has attempted to suppress. These discoveries include, but are not limited to: Earth’s nickel-silicide inner-core composition, the physical impossibility of both mantle convection and Earth-core convection; recognition that Earth’s early formation as a Jupiter-like gas giant makes it possible to derive virtually all geological and geodynamic behavior of our planet, including origin of continents and oceans, ocean floor topography, origin of mountains characterized by folding, primary initiation of fjords and submarine canyons, and two previously unanticipated potentially variable energy sources - nuclear fission and stored energy of protoplanetary compression; nuclear-fission-reactor origin of planetary magnetic fields, including the geomagnetic field; thermonuclear ignition of stars and the reason why the multitude of galaxies display just a few patterns of luminous stars; and, particulate pollution, not greenhouse gases, as the main cause of local and global warming. A scientific community, apparently suffering from Integrity Deficit Syndrome, cannot be expected to provide a truthful assessment, especially when queried about the actions of a president who might change the science landscape under which they flourish.